(untitled) (Research, Society and Development, 2020)
Objective: to identify the applicability of Heart Rate Variability (HRV) as a biomarker of stress through an integrative literature review. Method: for this purpose, a search was conducted in the Web of Science ® and Medical Literature Analysis and Retrieval System Online (MEDLINE) databases. The descriptors Heart Rate Variability, HRV, Autonomous Nervous System (ANS), RR Intervals and stress were combined in different ways in order to allow greater capture of studies. Inclusion criteria were studies involving humans, association between HRV and stress or ANS, and HRV analysis using linear and non-linear measurements. Eighteen publications were identified that met the inclusion and exclusion criteria. A descriptive analysis of these works was carried out. Results: the results showed that HRV characteristics were altered in response to stress. HRV indices obtained by linear methods (time domain and frequency domain) and non-linear methods were cited in some studies as a clinical diagnostic tool to investigate cardiovascular interactions, evaluate physiological mechanisms and trace their changes in different physiological states. Conclusion: it is concluded that HRV can be used to evaluate stress because it reflects cardiac activity and ANS activities. It was observed that the different methods used to induce stress were able to stimulate an ANS response through the changes in HRV parameters.